International Council for Standardization in Haematology (ICSH) recommendations for laboratory measurement of ADAMTS13. (16th July 2020) - Mackie, Ian; Mancini, Ilaria; Muia, Joshua; Kremer Hovinga, Johanna; Nair, Sukesh; Machin, Sam; Baker, Ross
Abstract: This guidance document was prepared on behalf of the International Council for Standardization in Haematology (ICSH), by the ADAMTS13 Assay Working Group, which comprises an international group of both clinical and laboratory experts. The document provides recommendations on best practice for the performance of ADAMTS13 assays in clinical laboratories. ADAMTS13 assays support the differential diagnosis of thrombotic microangiopathies and have utility in the management of thrombotic thrombocytopenic purpura (TTP). There are three types of assay: activity, antigen and autoantibody/inhibitor assays. Methods for activity assays differ in terms of sensitivity, specificity, precision and turnaround time. The most widely used assays involve VWF peptide substrates and either chromogenic ELISA or FRET techniques, although chemiluminescence assays and rapid screening tests have recently become available. Tests for autoantibodies and inhibitors allow confirmation of acquired, immune‐mediated TTP, while antigen assays may be useful in congenital TTP and as prognostic markers. In this document, we have attempted to describe ADAMTS13 assays and the conditions that affect them, as well as: blood collection, sample processing, quality control, standardization and clinical utility; recognizing that laboratories in different parts of the world have varying levels of sophistication. The recommendations are based on expert opinion, published literature and good clinical laboratory practice.